2018
DOI: 10.1080/17425247.2018.1546693
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drug delivery vehicles using atomic force microscopy: current status

Abstract: Introduction: The field of nanomedicine, utilising nano-sized vehicles (nanoparticles and nanofibres) for targeted local drug delivery, has a promising future. This is dependent on the ability to analyse the chemical and physical properties of these drug carriers at the nanoscale and hence atomic force microscopy (AFM), a high-resolution imaging and local force-measurement technique, is ideally suited. Areas covered: Following a brief introduction to the technique, the review describes how AFM has been used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 103 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…It can be observed that the nanoparticles are dispersed and do not form agglomerations. This can be attributed to surface modification, which makes the nanoparticles more stable by acting as a solvation layer and preventing interactions between SiO2 nanoparticles 83,102,103 .…”
Section: Characterization Of Dox@nanoformulationmentioning
confidence: 99%
“…It can be observed that the nanoparticles are dispersed and do not form agglomerations. This can be attributed to surface modification, which makes the nanoparticles more stable by acting as a solvation layer and preventing interactions between SiO2 nanoparticles 83,102,103 .…”
Section: Characterization Of Dox@nanoformulationmentioning
confidence: 99%
“…Scanning probe microscopies (i.e. atomic force microscopy and scanning tunneling microscopy) provide very high resolution and have been applied in the study of nanoscale structures 19,20 . Progress has also been reported by using electron microscopy, in studies of epitope distributions in protein complexes 21 and nanoparticles 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The type of DDS is usually chosen depending on the target cell surface receptor or organ or tissue and the structure of the therapeutics being delivered. The categories of carriers for these systems include cellular carriers (live cell and virus), particle carriers (microspheres, polymeric micelles, nanoparticles, liposomes, solid lipid particles, and polymeric systems), and soluble carriers like peptides, proteins, and polysaccharides (Smith et al, 2018). Among these abovementioned carriers, particle-based carriers have great potential.…”
Section: Improving Drug Delivery Approaches With Afmmentioning
confidence: 99%